STRATEGI PENGEMBANGAN MODEL KELEMBAGAAN KEMITRAAN AGRIBISNIS HORTIKULTURA DI BALI - INDRANINGSIH, KURNIA SUCI; -, ASHARI; FRIYATNO, SUPENA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008, 2012)
The role of horticulture commodities is very importance to enhance the growth of agriculture sector, and its elasticity causes the changing of income. To fill the market demand and consumer preference, the constrains related to efficiency, productivity, and quality of horticulture commodities should be attended seriously and to be as priority efforts. The solution to achieve those conditions is creating the partnership institution that farmers and other stakeholders can take benefit for each other and practice a good quality management. Bali province is one of famous region in Indonesia which has a high-market demand on horticulture commodities. The study aim to present identification results of partnership pattern, constrain, and it’s potency in Bali. Further, the formulation of alternative partnership models instead of existing partnership models also will be discussed. The result showed that generally, partnership pattern have been existing in Bali i.e.: plasm-nucleus model, agribusiness operational cooperative, farmers–sub terminal agribusiness (STA) cooperative and reguler trading. The efforts to improve agribusiness partnership model can be implemented through: (1) developing horticulture farmers association, (2) increasing market service information, (3) pushing the role of field extension worker, (4) building the vertical communication networking among agribusiness actors, (5) improving the Sub Terminal Agribusiness infrastructure, and (6) empowering the financial institution.
Keywords: Horticulture, Agricultural Sector, Partnership, Bali.